Regency of Bandung Civic Center (Bali): Evaluation of An Attempt of Making Cosmoreligious Landscape - T. Nirarta Samadhi (Journal of Regional and City Planning, 2001)
Bali is a unique place mainly due to its existence as an island populated mostly by Balinese Hindu. As such the Balinese traditional-religious conceptions of space are influential in the landscapes design. This paper examines the site plan and landscape design of Regency of Badung Civic Center in the Province of Bali Indonesia k describes the design approach taken by its designers, in which they explored the traditional-religious conceptions of space in relation to the design goals. The Balinese urban design objectives as proposed by Samadhi (2001 a, b) will be utilized as the tool of evaluation.